The Comparison of Ideational Meanings Conveyed by the Novice and Professional Presenter in Multimodal Presentations - Ni Putu Era Marsakawati (Universitas Muhammadiyah Semarang, 2018)
The paper reports on the result of a study aiming to investigate the comparison of ideational meanings conveyed by the novice and professional presenter in multimodal presentations. The study used a qualitative approach, especiallya videography research design, involving two presenters: a novice presenter and a professional one. The video data of the two presenters’ performance were selected as sources of data. The collected data were analyzed by administering a multi-layer analysis.The results show that: a) in terms of language, both presenters used two most dominant types of Processes: relational and material. However, a delicate analysis indicated that the professional presenter used relational processes more than the novice one; and b) in terms of gesture, both presenters realized ideational meanings through indexical gestures the most. However, a detailed analysis revealed that the professional presenter employed more gestures than the novice one. The study exploresa pedagogical implication for teachers/lecturers, material designers, and policy makers to provide a balanced emphasis on language and gesture used by the studentseither in the teaching and learning activities or in the designed learning materials.